Taxonomy of the family Strongylophthalmyiidae (Diptera: Nerioidea) in Korea - Junyeong Woo; Sang Jae Suh (Journal of Asia-Pacific Biodiversity, 2025)
The family Strongylophthalmyiidae is a poorly known taxon in Korea, and only two species, Strongylophthalmyia ustulata Zetterstedt, 1847, and Strongylophthalmyia raricornis Shatalkin, 1981 have been recorded until now. In the present study, the Korean Strongylophthalmyiidae was taxonomically reviewed, and five species were treated. Among them, three species, Strongylophthalmyia crinita Hennig, 1940; Strongylophthalmyia vikhrevi Galinskaya & Shatalkin, 2018; and S. tangwangana Zhou, Evenhuis & Yang, 2023, were first recorded in Korea.